2016
DOI: 10.1002/rev3.3054
|View full text |Cite
|
Sign up to set email alerts
|

Do some schools narrow the gap? Differential school effectiveness revisited

Abstract: Relatively little research has explored whether schools differ in their effectiveness for different group of pupils (e.g. by ethnicity, poverty or gender), for different curriculum subjects (e.g. English, mathematics or science) or over time (different cohorts). This paper uses multilevel modelling to analyse the national test results at age 7 and age 11 of over 6000 pupils attending 57 mainstream primary schools over three successive years in a socially and ethnically diverse inner London borough. The pupil g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 62 publications
6
22
1
3
Order By: Relevance
“…This suggests that countervailing effects (such as a tendency for schools with high EAL rates to also have high FSM rates) are at play and so the multivariate results are likely to be more accurate as an estimate of effect for this variable. The negative association between FSM and VA performance at school level is in line with the recent study by Strand () who found a negative cohort‐level association between FSM and performance even after controlling for individual pupil FSM status. Pupil‐level analyses in the present study (see later) found that FSM eligibility was associated with lower performance of about 0.33–0.46 NC points, varying according to which other contextual variables were accounted for in the CVA model.…”
Section: Results From Analysis 1 ‐ Observable Biasessupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that countervailing effects (such as a tendency for schools with high EAL rates to also have high FSM rates) are at play and so the multivariate results are likely to be more accurate as an estimate of effect for this variable. The negative association between FSM and VA performance at school level is in line with the recent study by Strand () who found a negative cohort‐level association between FSM and performance even after controlling for individual pupil FSM status. Pupil‐level analyses in the present study (see later) found that FSM eligibility was associated with lower performance of about 0.33–0.46 NC points, varying according to which other contextual variables were accounted for in the CVA model.…”
Section: Results From Analysis 1 ‐ Observable Biasessupporting
confidence: 90%
“…The official VA measures analysed earlier are largely based on standardised examinations and so inconsistent teacher assessment cannot be the source of the instability in that case. Also note that mathematics scores were used in an attempt to ensure measure reliability, recent research suggests that the consistency of English scores will be considerably lower (Strand, ). Further research may wish to replicate these results using more robust tests to estimate the extent to which teacher assessment contributes to inconsistency between cohorts, especially as teacher assessments are used extensively for KS1, KS2 and KS3 assessment as well as being used in day‐to‐day decisions about performance, curriculum and even teacher pay in English schools.…”
Section: Results From Analysis 3 – Consistency In Cohort Performancesmentioning
confidence: 99%
“…Our results suggest that school performance estimates based on a single cohort do not predict future performance. These levels of instability are consistent with the low to moderate correlations across cohorts found in recent research by Perry () and Strand (). This instability may be a result of transitory changes (i.e.…”
Section: Discussion Implications and Concluding Remarkssupporting
confidence: 90%
“…However, since the turn of the century, the implementation of ability grouping throughout the United States has increased markedly (Loveless, ). During this interval, educational research primarily focused on the relationship between ability grouping and the so‐called “achievement gap” (disparities in standardized test scores), especially for secondary school students (Schofield, ; Strand, ). Although a relationship may exist between participation in special science programs in middle‐schools and the pursuit of specialized STEM learning in high school, a literature search we carried out revealed no recent studies that explored this issue.…”
Section: Theoretical Backgroundmentioning
confidence: 99%